Dari Nada ke Rupiah: Memahami Kontrak Pencipta Lagu dengan Aggregator Musik - Muhammad Ryan Jahrul; Muh. Akbar Fhad Syahril (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study aims to examine the form of agreement between songwriters and music aggregators in Sidenreng Rappang Regency. Using normative and empirical legal research methods, this study found that agreements are generally in the form of standard contracts prepared by aggregators. The main challenges in the implementation of the agreement include the collection and distribution of royalties. Although registration is not mandatory for copyright validity, it makes it easier to prove in the event of a dispute.